Nodular mastocytosis: a case study - E. V. Pavlova; I. V. Ulitina; YU. E. Rusak; E. N. Efanova; E. N. Ivannikova (State Scientific Center of Dermatovenereology and Cosmetology, 2017)
A case study of nodular mastocytosis is described. Tacrolimus was used to treat skin manifestations of mastocytosis.